CUSTOMS CLEARANCE ISSUES CONCERNING MANAGEMENT OF LOGISTICS PROVIDER ACTIVITIES IN RAILWAY TRANSPORTATION - Y. Zaletov; V. Ostapchuk (Вестник университета, 2016)
The article examines the significance of mastering the customs clearance of export and import cargoes by existing companies providing comprehensive services on the international freight market - logistics providers. The study covers the brief history of logistics provider work formation in the transportation industry. The focus is on the international rail traffic aspect. The paper gives suggestions on the customs clearance development in the system of logistics providers.